Enhancing Academic Well-Being in Bangladesh: Lessons from School Culture Research - Ahmed, MD. Faisal (Utan Kayu Publishing, 2025)
The education system in Bangladesh remains heavily exam-oriented, often at the expense of students’ psychological well-being and holistic development. This article explores how reforming school culture—defined as the network of beliefs, practices, and relationships that shape the learning environment—can enhance academic well-being. Drawing from global best practices and empirical studies, particularly in socio-economically similar contexts, the article advocates for integrating socio-emotional learning (SEL), improving teacher training, reducing educational inequality, and implementing constructivist or project-based assessment methods. These interventions can create a more inclusive, student-centered environment that promotes both academic success and emotional resilience. The scope of this article is conceptual and policy-oriented, aiming to synthesize evidence and propose actionable strategies rather than report findings from original empirical research. Limitations include the absence of primary data and the need for contextual adaptation of international models to Bangladesh’s unique socio-cultural setting. Practical implications of SEL integration include improved classroom climate, reduced student anxiety, and enhanced interpersonal skills—factors increasingly vital for 21st-century education. Ultimately, the article emphasizes that fostering positive school culture is essential for sustainable education reform in Bangladesh.